Controlled direct growth of Al2O3-doped HfO2 films on graphene by H2O-based atomic layer deposition. Issue 5 (18th December 2014) - Zheng, Li; Cheng, Xinhong; Yu, Yuehui; Xie, Yahong; Li, Xiaolong; Wang, Zhongjian
Abstract : Al2 O3 -doped HfO2 with both amorphous state and high relative permittivity was directly deposited on graphene by atomic layer deposition. Abstract : Graphene has been drawing worldwide attention since its discovery in 2004. In order to realize graphene-based devices, thin, uniform-coverage and pinhole-free dielectric films with high permittivity on top of graphene are required. Here we report the direct growth of Al2 O3 -doped HfO2 films onto graphene by H2 O-based atom layer deposition (ALD). Al2 O3 -onto-HfO2 stacks benefited the doping of Al2 O3 into HfO2 matrices more than HfO2 -onto-Al2 O3 stacks did due to the micro-molecular property of Al2 O3 and the high chemical activity of trimethylaluminum (TMA). Al2 O3 acted as a network modifier, maintained the amorphous structure of the film even to 800 °C, and made the film smooth with a root mean square (RMS) roughness of 0.8 nm, comparable to the surface of pristine graphene. The capacitance and the relative permittivity of Al2 O3 -onto-HfO2 stacks were up to 1.18 μF cm −2 and 12, respectively, indicating the high quality of Al2 O3 -doped HfO2 films on graphene. Moreover, the growth process of Al2 O3 -doped HfO2 films introduced no detective defects into graphene confirmed by Raman measurements.